2010
DOI: 10.1590/s0103-507x2010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de sistema fechado para coleta de sangue e necessidade de transfusão em pacientes graves

Abstract: Utilização de sistema fechado para coleta de sangue e necessidade de transfusão em pacientes graves ORIGINAL ARTICLE Conflicts of interest: Edwards Lifesciences (Irvine-CA) supplied the closed systems for blood sampling (VAMP ®-Venous Arterial Blood Management Protection). No financial support was involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We identified eight RCTs which evaluated blood conservation devices, six with arterial lines [119][120][121][122][123][124][125], and one with PICC lines [126]…”
Section: Evidence Summarymentioning
confidence: 99%
“…We identified eight RCTs which evaluated blood conservation devices, six with arterial lines [119][120][121][122][123][124][125], and one with PICC lines [126]…”
Section: Evidence Summarymentioning
confidence: 99%
“…Although three studies did not observe a statistically significant decrease in hemoglobin concentration (33–35), one study reported a statistically significant hemoglobin decline in their control patients compared with those with the VAMP device (∆hemoglobin = –21.3 ± 23.2 g/L vs –14.4 ± 20.8 respectively, p = 0.02) (30). Another study similarly observed a significant difference in final hemoglobin between both groups (VAMP hemoglobin 104 ± 23.7 to 97 ± 13 g/L vs controls hemoglobin 105 ± 22.4 to 91 ± 18.0g/L; p = 0.006) (21). Only two studies observed a significant decrease in transfusion number in the intervention group (30, 33).…”
Section: Resultsmentioning
confidence: 84%
“…Seven research groups evaluated the use of an arterial closed blood sampling device in adult patients: one was a pre-post trial with a subgroup analysis published subsequently (29,30), one was a prospective crossover study (31), and five were RCTs (21,(32)(33)(34)(35). Four studies compared diagnostic blood loss with the venous-arterial blood management protection (VAMP) device versus standard blood sampling (31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that minimizing blood wasting should be an important intervention to introduce into clinical practice. Blood conservation devices can help to reduce the amount of blood wasted for line rinsing (21,(28)(29)(30)(31)(32)(33). Arterial closed blood sampling devices such as the Venous-Arterial blood Management Protection device can significantly lower the amount of blood volume discarded (28)(29)(30)34).…”
Section: Discussionmentioning
confidence: 99%